Circumscription, diagnosis and description of two subfamilies and one genus of Australo-Papuan robins (Aves: Passeriformes: Petroicidae) - Christidis, Leslie; Irestedt, Martin; Rowe, Dianne; Boles, Walter E.; Norman, Janette A. (Zootaxa, 2012)
Christidis et al. (2011) conducted a phylogenetic study of the Australo-Papuan robins (Aves: Passeriformes: Petroicidae) and erected three new taxa: two subfamilies, Amalocichlinae and Pachycephalopsinae, and a genus, Cryptomicroeca.  Following the requirements of Article 11.7 of the International Code of Zoological Nomenclature (ICZN 1999), these were created giving their circumscription, i.e., the lower taxa included in each, respectively.  Additional requirements for the erection of these new taxa, as set out in Article 13.1 (ICZN 1999), however, were unfortunately not met.  This Article (13.1.1) requires that the formation of a new name, in this case at both family and generic level, also provides a description or definition stating in words the characters that purportedly differentiate it from other taxa.  This requirement was not met in Christidis et al. (2011), so we rectify this omission here.  A similar problem that arose with the erection of the robin subfamily Microecinae by Loynes et al. (2009) was subsequently corrected by Loynes et al. (2011).